HUBUNGAN ANTARA KESEPIAN DAN OBESITAS: META-ANALISIS STUDI OBSERVASIONAL - Tursina, Elsa; Hikmah, Annisa Arifatul; Fatony, Riska Fajar; Yusuf, Muhammad (Rena Cipta Mandiri, 2025)
Loneliness has been increasingly recognized as a psychosocial factor influencing obesity risk. However, findings from individual studies remain inconsistent. This meta-analysis aimed to analyze and estimate the pooled association between loneliness and obesity. A meta-analysis study using the PICO framework, adults (population), loneliness (intervention), not lonely (comparison), and obesity (Outcome). A search was conducted in PubMed, ScienceDirect, and Scopus databases for studies published between 2015 and 2025 following PRISMA guidelines. Search terms used were: (